A study on the relationship between the big five personality and job performance among employees at FGV Agri Services Sdn. Bhd, Jerantut, Pahang / Nur Azniza Amiruddin - Amiruddin, Nur Azniza (Faculty of Business and Management, 2020)
The purpose if this research was to investigate the relationship between the Big Five Personality and job performance among employees in selected departments in FGV Agri Services Sdn. Bhd., Jerantut, Pahang. This correlational research used a stratified random sampling techniques and the sample size was determined using Krejcie and Mogan (1970). Survey questionnaires were distributed to 140 employees in selected departments. The questionnaire were analysed using SPSS V-23 to identify the result. Most of the respondents were male; aged above 41 years old, married, attained SPM qualification and have above 21 years working experience. The finding showed that the majority of employees of FGV Agri Services are having conscientiousness as the result presented that the highest mean scored with (M=4.442, SD=0.38043). Moreover, as conscientiousness indicates the highest mean scored (M=4.442, SD=O.38043) and the lowest mean scored is neuroticism with the total mean scored is (M= 3.9137, SD= 61803). It can be concluded that this personality trait is most affecting the employees' job performance. Whereas the lowest mean is neuroticism, indicate that employees of FGV Agri Services Sdn. Bhd are positively influenced in performing their work due to this kind of personality. The correlation result showed that the Big Five Personality has a positive relationship with job performance. It is recommended that organization develop a self-improvement program for employees and provide employer's mentoring and monitoring. Finally, future study should focus on conduct the study with a large sample size, use the upper level of employees as a unit of analysis, and carried out the study in both the government sector and private companies in Malaysia